The Intestinal Microbiota and Colorectal Cancer - Cheng, Yiwen; Ling, Zongxin; Li, Lanjuan (Frontiers in Immunology, 2020)
The intestinal microbiota, composed of a large population of microorganisms, is often considered a “forgotten organ” in human health and diseases. Increasing evidence indicates that dysbiosis of the intestinal microbiota is closely related to colorectal cancer (CRC). The roles for intestinal microorganisms that initiated and facilitated the CRC process are becoming increasingly clear. Hypothesis models have been proposed to illustrate the complex relationship between the intestinal microbiota and CRC. Recent studies have identified Streptococcus bovis, enterotoxigenic Bacteroides fragilis, Fusobacterium nucleatum, Enterococcus faecalis, Escherichia coli, and Peptostreptococcus anaerobius as CRC candidate pathogens. In this review, we summarized the mechanisms involved in microbiota-related colorectal carcinogenesis, including inflammation, pathogenic bacteria, and their virulence factors, genotoxins, oxidative stress, bacterial metabolites, and biofilm. We also described the clinical values of intestinal microbiota and novel strategies for preventing and treating CRC.